A transient nanoscale flow model for alkanes considering inhomogeneous flow properties and rough surfaces - Cao, Cheng; Chang, Bin; Yang, Zhao; Yong, Longquan; Li, Changzhou (Journal of molecular liquids, 2024)
•Density and viscosity models that characterize the properties of inhomogeneous flow are developed.•A transient numerical model that describes the transport behavior of alkanes in unsteady and steady stages is proposed.•Revealing the alkane flow behavior with the combined effect of nanoconfinement effects and rough nanochannels. The flow of alkanes within nanochannels holds significant scientific implications for biological, material, and oil field development. Existing models often overlook the combined effect of transient transport and rough surfaces under nanoconfinement conditions. In this study, we formulated an inhomogeneous density model controlled by wall energy based on molecular simulation results. Additionally, we constructed an inhomogeneous viscosity model by combining excess free energy, solvation energy, and cohesion energy using the Eyring equation. Integrating these models with the Weierstrass-Mandelbrot fractal function and a modified Navier-Stokes equation yielded a novel transient nanoscale flow model. We iteratively solved the model using the finite element method and confirmed model validity through comparisons with experimental data, molecular dynamics simulations, and existing models. Key findings indicated that surface roughness inhibited pressure drop deceleration caused by nanoconfinement. Conversely, rough surfaces and an inhomogeneous viscosity contributed to an increased pressure drop, moderated by slip effects. In the unsteady stage, the variation in flow enhancement rate was intricate and contingent on the combined action of rough surfaces and nanoconfinement effects at distinct times. Notably, the influence of inhomogeneous density on the flow enhancement rate initially amplified and then diminished, gradually dissipating over time. In the steady stage, inhomogeneous viscosity facilitated volumetric flux in smaller sizes (2 nm) but hindered it in larger sizes (10 nm).